[Ge2S5(S2)]4−, A NLO‐Active Unit Leading to an Asymmetric Structure Discovered in Li2Cs4Ge2S5(S2)Cl2: An Experimental and Theoretical study. Issue 21 (26th March 2019) - Li, Guangmao; Wu, Kui; Huang, Yi; Yang, Zhihua; Pan, Shilie
Abstract: Metal‐centered MS4 tetrahedra are fundamentally important building blocks for the structural construction of infrared (IR) nonlinear optical (NLO) mateirals, because they have a large effect on properties like second‐harmonic generation, birefringence, band gap, etc. Therefore, rational design and selection of these tetrahedra could effectively help synthesize new materials and give satisfactory properties. In this work, we reported a new NLO‐active [Ge2 S5 (S2 )] 4− unit composed of two corner‐shared GeS4 tetrahedra with a nonpolar covalent S−S bond, discovered in a new compound of Li2 Cs4 Ge2 S5 (S2 )Cl2 . To the best of our knowledge, this [Ge2 S5 (S2 )] 4− unit has never been discovered. [Ge2 S5 (S2 )] 4− units have intrinsic asymmetric features and lead to the whole structure being noncentrosymmetric (NCS). Further, real‐space atom‐cutting methods reveal that they make almost all the contribution to the second‐harmonic generation response (SHG) for Li2 Cs4 Ge2 S5 (S2 )Cl2 . All of the above indicate that the [Ge2 S5 (S2 )] 4− unit is a new functional unit and a good choice for designing new IR NLO materials. Abstract : Nonlinear optical materials : A fundamental building unit, [Ge2 S5 (S2 )] 4− dimer, discovered in thiogermanate Li2 Cs4 Ge2 S5 (S2 )Cl2, makes almost all the contribution to the SHG response of Li2 Cs4 Ge2 S5 (S2 )Cl2 (see figure).